Sistem pengelolaan informasi dan manajemen laboratorium komputer Jurusan Teknik Elektro Politeknik Negeri Banjarmasin - Herri Apriana; Puspa Ayu Yohana (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2019)
The function of the Banjarmasin State Polytechnic Electrical Engineering Laboratory is not only as a place for practicum of electrical engineering courses, but also as a place to research for students and lecturers. This study aims to design and build applications to control practicum activities in the Electrical Engineering Laboratory. This application program is made by utilizing client server technology, where the client is the computer used for the practicum, while the server is a computer that is used specifically to manage the client. For client and server interfaces using the Borland Delphi 7 desktop program. The results of the research that have been carried out are the Management System of the Electrical Engineering Laboratory in the form of a Laboratory Management Application.